Pregnant women's experiences of social distancing behavioural guidelines during the Covid-19 pandemic 'lockdown' in the UK, a qualitative interview study - Emma Anderson; Amberly Brigden; Anna Davies; Emily Shepherd; Jenny Ingram (BMC, 2021)
Abstract Background Covid-19 triggered the rapid roll-out of mass social distancing behavioural measures for infection control. Pregnant women were categorised as 'at risk' requiring extra vigilance with behavioural guidelines. Their understanding and ability to adhere to recommendations was unknown. Objectives To complete a behavioural analysis of the determinants of recommended social distancing behaviour in pregnant women, according to the 'capability, opportunity, motivation and behaviour' ('COM-B') model to inform the development of recommendations/materials to support pregnant women in understanding and adhering to behavioural guidelines. Design Qualitative interview study with pregnant women in the Bristol area (UK). Methods Semi-structured telephone/videoconference interviews were conducted following a topic guide informed by the COM-B model, transcribed verbatim and subjected to framework analysis. Infographic materials were iteratively produced with stakeholder consultation, to support pregnant women. Results Thirty-one women participated (selected for demographic range). Women reported adhering to social distancing recommendations and intended to continue. COM-B analysis identified gaps in understanding around risk, vulnerability, and the extent of required social distancing, as well as facilitators of social distancing behaviour (e.g. social support, motivation to stay safe, home environment/resources). Additional themes around detrimental mental health effects and changes to maternity healthcare from the social distancing measures were identified. Infographic resources (plus midwife report) addressing women's key concerns were produced and disseminated. Conclusions The COM-B model provided useful details of determinants of pregnant women's adherence to social distancing behaviours. The confusion of what being 'at risk' meant and varying interpretation of what was expected indicates a need for greater clarity around categories and guidance. The loss of maternity care and negative mental health effects of social distancing suggest a growing area of unmet health needs to be addressed in future.